The Use of Songs as a Medium for English Learning: A Case Study at SDN Maliwuko - Ingriyani Yohana Rawung; Sitti Fitriawati (Sintuwu Maroso Journal of English Teaching, 2025)
This study investigates the use of songs as a medium for English language learning among fourth- and fifth- grade students at SDN Maliwuko, Poso Regency, Indonesia. Conducted over a two-month period (January–February2025), the research employed a descriptive qualitative case study approach. Data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation of lesson plans and learning modules. The findings reveal that songs were integrated into all stages of the learning process: preliminary, core, andfinal act  vities. During preliminary activities, songs functioned as ice-breakers to motivate students and prepare them psychologically for learning. In core activities, songs were used to introduce and reinforce vocabulary, improve pronunciation, and associate words with physical movements, thereby integrating cognitive, affective, and psychomotor domains. In final activities, songs served as closing exercises and informal evaluation tools. Interviews with the teacheremphasized  the  importance  of  creativity  in  selecting  and  implementing  songs,  highlighting  their  effectiveness  in increasing student motivation, maintaining concentration, and creating a lively classroom atmosphere. Student interviews confirmed these benefits, with most students reporting that songs made learning enjoyable and helped them memorize vocabulary more easily. However, challenges were noted when song lyrics were too long, underscoring the need forcareful song selection. Overall, the study concludes that songs are an effective pedagogical medium for English language learning in  Indonesian  elementary schools. They foster  motivation, concentration, and  enjoyment while supporting vocabulary acquisition and pronunciation practice. The integration of songs into English learning reflects an innovative and responsive approach aligned with the principles of the Merdeka Curriculum.